TOPOGRAPHIC ANATOMY AS A BASIS FOR MINIMALLY INVASIVE SURGERY - Suyunova Zamira Axatovna; Awaish Asim (TADQIQOTLAR, 2025)
Abstract The advancement of minimally invasive surgery has transformed clinical practice, reducing postoperative pain, hospital stay, and recovery time. However, the success of laparoscopic and endoscopic procedures largely depends on precise knowledge of topographic anatomy. This article discusses the integration of anatomical principles into minimally invasive techniques and highlights their role in patient safety.